The effects of concurrent biomechanical biofeedback on rowing performance at different stroke rates - Gorman, A. J.; Willmott, A. P.; Mullineaux, D. R. (Journal of Sports Sciences, 2021)
The aims of this study were to assess the effects of stroke rate (SR) on the ability of trained rowers to: a) comply with concurrent biomechanical biofeedback on knee-back-elbow joint sequencing; and b) transfer any changes to competition-intensity conditions (maximal rowing task). Following a five-minute maximal rowing task (Baseline), 30 trained rowers were randomised to four groups. Two groups rowed at high SRs (90% maximum SR with biofeedback (BFb90) or control), while others rowed at low SRs (60% maximum SR with biofeedback (BFb60) or control) for 3 sessions. All rowers then completed another maximal rowing task (Transfer). Rowers complied with the biofeedback at both SRs, which promoted coordinative changes to knee-elbow motions during the pull. During Transfer, control rowers did not improve whereas those receiving biofeedback covered significantly greater distances (increase from Baseline: BFb60 = 6 ± 5%; BFb90 = 5 ± 4%; p < 0.05). However, movement adaptations were temporally different between SRs and were better maintained into Transfer by those that rowed at higher rates. This indicated biofeedback specificity, as transference of modified movement patterns appeared better when acquisition and transfer conditions were similar. These findings have practical implications for assimilating biofeedback into training programmes.